Axillary Lymph Node Dissection Can Be Omitted in Breast Cancer Patients With Mastectomy and False-Negative Frozen Section in Sentinel Lymph Node Biopsy - Si, Jing; Guo, Rong; Pan, Huan; Lu, Xiang; Guo, Zhiqin; Han, Chao; Xue, Li; Xing, Dan; Wu, Wanxin; Chen, Caiping (Frontiers in Oncology, 2022)
Background The IBCSG 23-01 and AMAROS trials both reported that axillary lymph node dissection (ALND) did not change survival rates in breast cancer patients with positive nodes detected by sentinel lymph node biopsy (SLNB). The aim of this study was to determine whether breast cancer patients with mastectomy and false-negative frozen section (FS) in SLNB could forgo ALND. Materials and methods This was a retrospective study of cN0 patients diagnosed with primary invasive breast cancer treated by mastectomy and SLNB at our institute between January 2010 and December 2014. Patients with false-negative FS in SLNB were separated by the following management in axillary into non-ALND group (non-process or axillary radiation only) and ALND group (with or without radiation). Results A total of 212 patients were included, 86 and 126 patients in non-ALND and ALND group, respectively. The positive rate of non-SLNs was 15.87% (20/126) in ALND group. In multivariate analysis, we found that patients with larger tumor size (>2cm) (OR 1.989, P=0.030) and multifocal lesions (OR 3.542, P=0.029) tended to receive ALND. The positivity of non-SLNs in ALND group was associated with SLN macrometastasis (OR 3.551, P=0.043) and lymphovascular invasion (OR 6.158, P=0.003). Also, removing more SLNs (≥3) was related to negativity in non-SLNs (OR 0.255, P=0.016). After a median follow-up of 59.43 months, RFS and OS of the two groups were similar (P=0.994 and 0.441). In subgroup analysis, we found that 97 patients who met the inclusive criteria of IBCSG 23-01 trial had similar RFS and OS between non-ALND and ALND group (P=0.856 and 0.298). The positive rate of non-SLNs was 9.62% (5/52). Also, in 174 patients who met the criteria of AMAROS trial, RFS and OS in non-ALND and ALND group were similar (P=0.930 and 0.616). The positive rate of non-SLNs was 18.27% (19/104). Conclusion ALND can be carefully omitted in selected breast cancer patients with mastectomy and false-negative FS in SLNB. SLNB is relatively sufficient in IBCSG 23-01-eligible patients, and axillary radiation was an effective option in AMAROS-eligible patients.